Craniodiaphyseal dysplasia, a very rare form of bone dysplasia - Bayar Ahmed Qasim; Ayad Ahmad Mohammed; Amer A. Balata; Sardar Hassan Arif; Laween Omar Musa (Oral and Maxillofacial Surgery Cases, 2020)
Introduction: Craniodiaphyseal dysplasia is a very rare autosomal recessive disorder which is typically presented in infancy and characterised by severe form of bone dysplasia, massive bone sclerosis and hyperostosis. This process of bone changes characteristically affects the facial bones resulting in severe facial deformity. Case presentation: A-25-year-old girl who was diagnosed as a case of juvenile Paget's disease for 20 years presented with blurred vision, chronic headache and recurrent attacks of sinusitis. Re-evaluation of the patient was done and gene study was done which excluded Paget's disease. On the basis of her clinical examination and after exclusion of other possible causes the case was diagnosed as craniodiaphyseal dysplasia. Conclusion: Craniodiaphyseal dysplasia causes progressive facial bone enlargement and deformity with narrowing of the orifices of sinuses and compression on various cranial nerves due to narrowing of the cranial nerve openings. Multidisciplinary team is usually needed for the diagnosis and the management of this unusual diseases. Gene study must be done to confirm or exclude other rare genetic disorders.